A PERSONAL LIBRARY OF KARL GOTTFRIED HAGEN, PROFESSOR OF KONIGSBERG UNIVERSITY (1749–1829) (in Russian) - JERMAKOVA, NADEŽDA (Knygotyra, 2015)
Karl Gottfried Hagen (1749–1829) was a famous German chemist, founder of Pharmacology, MD University of Koenigsberg, and the head of the family pharmacy business. Professor Hagen was a versatile lecturer: he lectured on chemistry, physics, mineralogy, zoology, botany at the University of Konigsberg. The son of Professor Hagen – E. A. Hagen – helped to publish “The Seasons” by K. Donelaitis. The library of Professor Hagen was one of the best in Konigsberg. In this article we have analyzed some qualitative and quantitative indicators of Professor Hagen’s library. For this purpose we considered his life events and scientific activities, and those historical events which influenced the development of Professor Hagen’s pedagogical views. The analysis of biographical facts and historical events that influenced Professor Hagen’s Path of life allowed us to identify the following three main types of his activities: scientific, educational and journalistic. The library in question played an important role in the organization of Hagen’s integrated productive activity. The Auction Catalogue “List of books of K. G. Hagen” served as the basis of our research. It was published in Konigsberg (1829) and consists of 128 pages. This document was put at our disposal by Dr. E. Neumann-Redlin von Meding, a descendant of Professor Hagen. Traditionally, we have analysed the information in the following areas: place of publication; year of publication; scientific fields; language of publication; types of publications and documents. There are over 100 places of publication in the Catalogue. We have established that the Catalogue of Hagen’s library contains the following sections: history of science; physics; chemistry; alchemy; zoology; botany; mineralogy; medicine and related sciences; history of Prussia; philosophy, theology and related sciences. The Catalogue includes such types of publications as textbooks, monographs, dictionaries, manuals and guidelines, pharmacopoeia, dissertations, manuscripts, scientific journals, descriptions of travel, newspapers. To the best of our knowledge, only part of Hagen’s publications was offered in the auction. We hope to continue the search for more relevant information. We believe that it will promote modern lecturers’ and students’ information competence and develop the dialogue “library – reader”.